Males Are Capable of Long-Distance Dispersal in a Social Bee - Garcia Bulle Bueno, Francisco; Garcia Bulle Bueno, Bernardo; Buchmann, Gabriele; Heard, Tim; Latty, Tanya; Oldroyd, Benjamin P.; Hosoi, Anette E.; Gloag, Rosalyn (Frontiers in Ecology and Evolution, 2022)
Pollinator conservation is aided by knowledge of dispersal behavior, which shapes gene flow and population structure. In many bees, dispersal is thought to be male-biased, and males’ movements may be critical to maintaining gene flow in disturbed and fragmented habitats. Yet male bee movements are challenging to track directly and male dispersal ability remains poorly understood in most species. Here, we combine field manipulations and models to assess male dispersal ability in a stingless bee (Tetragonula carbonaria). We placed colonies with virgin queens at varying distances apart (1–48 km), genotyped the males that gathered at mating aggregations outside each colony, and used pairwise sibship assignment to determine the distribution of likely brothers across aggregations. We then compared simulations of male dispersal to our observed distributions and found best-fit models when males dispersed an average of 2–3 km (>2-fold female flight ranges), and maximum of 20 km (30-fold female flight ranges). Our data supports the view that male bee dispersal can facilitate gene flow over long-distances, and thus play a key role in bee populations’ resilience to habitat loss and fragmentation. In addition, we show that the number of families contributing to male aggregations can be used to estimate local stingless bee colony densities, allowing population monitoring of these important tropical pollinators.